1)
BaCO3 = BaO + CO2
n(BaCO3) = m/Mr = 19,7/197 = 0,1 моль
n(BaO) =n(BaCO3) = 0,1 моль
m(BaO) = n*Mr = 0,1* 153 = 15,3 г
V(CO2) = Vm* n = 22,4*0,1 = 2,24л
ответ 15,3 г и 2,24 л
2)
2N2 + 3H2 =2 NH3
28кг х кг теоритически
N2 + 3 Н2 = 2 NН3
28 кг 2·17кг
m (NН3)теоретич =(28·2·17):28=34кг
выход продукта= mпр : mтеор · 100% = 25,5 : 34 ·100 =75%
3)
CO2 + Ca(OH)2 = CaCO3 + H2O
n(CO2) = V/Vm = 6,72/22,4 = 0,3 моль
n(CaCO3) = 0,3 моль
m(CaCO3) = n*Mr = 0,3* 100 = 30 г
ответ 30 г.
4)Fe2O3 + H2 = Fe + H2O.
1)m(Fe2O3) = 16*0,8 = 12,8 г
2) n(Fe2O3) = m/Mr = 12,8/160 = 0,08 моль
3) n(Fe) = 0,08 моль
4)m(Fe) = 0,08*56 = 4,48г
ответ: 4,48 г
5)
MgO+ H2SO4 = MgSO4 + H2O
m(H2SO4) = 49*0,1 = 4,9 Г
n(H2SO4) = m/Mr = 4,9/98 = 0,05 моль
n(MgSO4) = 0,05 моль
m(MgSO4) = n*Mr = 0,05 * 120 = 6
ответ: 6 г.
CaO + 2HNO3 = Ca(NO3)2 + H2O
Ca(+2) + O(-2) + 2H(+1) + 2NO3(-1) = Ca(+2) +2NO3(-1) +H20
2H(+1) + O(-2) = H2O
2)
MgO + PO3 = бред. Может так:
3MgO + 2h3PO4 = Mg3(PO4)2 +3 H2O
3(MgO) + 2H(+1) + 2(PO4) (-3) = Mg3(PO4)2+ 3H2O
3MgO + 2H(+1) + 2(PO4) (-3) = Mg3(PO4)2
3)
Pb(NO3)2 + KI = PbI2 + 2KNO3
Pb(+2) + 2NO3 (-1) + K(+1) + I(-1) = PbI2 + 2K(+1) + 2NO3(-1)
Pb(+2) + I(-1) = PbI2
4)
MgO + K2CO3 = MgCO3 + K2O
Mg(+2) + O(-2) + 2K(-1) + CO3(-2) = MgCO3 + 2K(+1) + O(-2)
Mg(+2) + CO3(-2) = MgCO3
5)
Al2O3 + 3SO3 = Al2(SO4)3
2Al(+3) + 3O(-2) = Al2(SO4)3
6)
BaCl2+K2So4 = BaSO4 + 2KCl
Ba(+2) + 2Cl(-1) + 2K(+1) + SO4(-2) = BaSO4 + 2K(+) + 2Cl(-1)
Ba(+2) + SO4(-2) = BaSO4
7)
Zn+2H3PO4 = Zn3(PO4)2 + 3H2
Zn (+2) + 6H(+1) + 2PO4(-3) = Zn3(PO4)2 + 6H(+1)
Zn(+2) + 2PO4(-3) = Zn3(PO4)2
8)
BaO + CO2 = BaCO3
Ba(+2) + O(-2) = BaCO3
9)
MgSp4+Na2Co3 бред. может MgSO4?
MgSO4 + Na2CO3 = MgCO3 + Na2SO4
Mg(+2) + SO4(-2) + 2Na(+1) + CO3(-2) = MgCO3 + 2Na + SO4(-2)
Mg(+2) + CO3(-2) = MgCO3
10)
CuO + 2HNO3 = Cu(NO3)2 + H2O
Cu(+2) + O(-2) + 2H(+1) +2(NO3(-1) = Cu(NO3)2 + H2O
Cu(+2) + 2NO3(-1) = Cu(NO3)2
11)
ZnO + SO3 = ZnSO4
так и остается, т.к. оксиды не диссоциируют.
12)
FeCl3 + K3PO4 = FePO4 + 3KCl
Fe(+3) + Cl(-1) + 3K(+1) + PO4(-3) = FePO4 + 3K(+1) + 3Cl(-1)
Fe(+3) + PO4(-3) = FePO4
Объяснение:
А) K₂SiO₃ +H₂SO4 = H₂SiO₃↓+K₂SO4 2) образование осадка
Б) Cu(OH)₂↓ + 2HNO₃= Cu(NO₃)₂+2H₂O 3) растворение осадка
В) Na₃PO₄ + 3AgNO₃=3NaNO₃+Ag₃PO₄↓2) образование осадка